The Relationship Between Workplace Spirituality and Flourishing in Women Reviewed from Employment Status - Farisa Aqila; Agus Salim; Mustaqim Setyo Ariyanto (Jurnal Indonesia Sosial Teknologi, 2024)
Women's problems seem to be a theme that society will never forget. This issue is further strengthened by the role of women which begins to roll along with the development of the times. The Central Statistics Agency (BPS) noted that as of 2022 there are 133,542,018 female residents in Indonesia. This study aims to examine the relationship between workplace spirituality and flourishing in women, with an overview of job status. Through a quantitative approach with a correlational method, this study was conducted on 304 women in the Special Region of Yogyakarta, both working and non-working. The results showed that workplace spirituality had a positive effect on flourishing in women, and job status moderated this influence. Working women had higher rates of flourishing than those who did not work, suggesting that job roles provide meaning in daily life that affects psychological well-being. These findings emphasize the importance of promoting workplace spirituality in creating a balance between personal and professional lives, as well as improving women's psychological well-being.